Motivational role of teachers in developing English speaking skills of Pakistani university students - Younas, Muhammad; El-Dakhs, Dina; Anwar, Behzad; Jinag, Yicun (Frontiers in Education, 2025)
This research explores the motivational role of teachers in developing and enhancing the English-speaking skills of university students in Punjab Province, Pakistan. Mastery of English is essential since it is used as a global lingua franca in education, science, technology, business, and cultural exchange. However, psychological barriers, traditional teaching methods, and imbalanced assessment systems that place more emphasis on reading and writing rather than speaking hinder Pakistani students from acquiring proficiency in spoken English. The present study explores how teachers, as motivators, facilitators, and feedback providers, can help learners overcome these challenges with the help of a supportive classroom environment by fostering intrinsic motivational orientation of the learners. A quantitative research design in which data was collected from 200 teachers using questionnaires from different university teachers. Structural equation modeling (SEM) was conducted using Smart PLS 4.1.0.3 to test associations among motivational constructs, namely, teacher encouragement, classroom environment, and feedback mechanisms, with students’ willingness to communicate in English. The findings of the present study indicate positive and significant associations between teachers’ motivational strategies and students’ speaking proficiency. Self-esteem, anxiety reduction, and willingness to communicate were greatly influenced by teachers’ roles as motivators. However, despite these insights, systemic issues such as the lack of resources, outdated teaching materials, and limited use of technology are some of the setbacks identified in the study. The results point out the need for institutional reforms and teacher training programs focusing on communicative language teaching. The study contributes to an understanding of the pivotal role teachers play in motivating EFL learners and offers practical recommendations to improve speaking skills in English in non-native contexts.